Doing Formal Grounded Theory - Tom Andrews (Grounded Theory Review: An International Journal)
This is the latest in a family of Grounded Theory books by Glaser that continue to build on previous work and make the methodology much more explicit. Its purpose is quite simply to provide Grounded Theory researchers with a set of procedures that can be followed to generate a Formal Grounded Theory (FGT). Despite several chapters in previous books that deal with generating formal grounded theory it has been given scant attention by researchers and this book aims to reverse this. It brings together and synthesises these previous writings in one book and seeks to specify much more clearly what is meant by a formal grounded theory. As with other more recent books by Glaser, this one is based on data in that the procedures outlined are come from previously generated formal grounded theories. However, Glaser cautions that this is based on limited data since not many FGTs exist yet and as more are generated, the method will become more explicit. The book has been eagerly anticipated by grounded theorists and it does not disappoint.